2021
DOI: 10.1039/d1nj03123f
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective visible-light-triggered CO2 fixation to cyclic carbonates under mild conditions using TiO2/multiwall carbon nanotubes (MWCNT) grafted with Pt or Pd nanoparticles

Abstract: Irradiation of a series of aromatic epoxides and CO2 in presence of TiO2, TiO2/MWCNT, Pt//TiO2/MWCNT and Pd/TiO2/MWCNT photocatalysts was investigated with visible light- induced cycloaddition reaction for the production of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…22 Elgohary et al reported the use of TiO 2 bound multiwall carbon nanotubes (MWCNT) doped with Pt or Pd nanoparticles as visible light active photocatalysts for the chemical fixation of CO 2 to cyclic carbonates. 23 However, the reported methods suffer from the drawbacks of using toxic and costly metallic or photocatalysts involving multi-step and cumbersome synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…22 Elgohary et al reported the use of TiO 2 bound multiwall carbon nanotubes (MWCNT) doped with Pt or Pd nanoparticles as visible light active photocatalysts for the chemical fixation of CO 2 to cyclic carbonates. 23 However, the reported methods suffer from the drawbacks of using toxic and costly metallic or photocatalysts involving multi-step and cumbersome synthetic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the preceding results and discussion, as well as the literature reports, , a plausible mechanism for the 1 -catalyzed cycloaddition reaction of CO 2 to an epoxide is shown in Scheme . Because 1 or TBAB cannot catalyze the reaction proficiently on their own, their coparticipation could be clearly established.…”
Section: Results and Discussionmentioning
confidence: 68%
“…This can be attributed to their low concentrations, low diffraction peak intensities, or their peaks became thinner after composite formation, causing the noticed displacements in peak positions, overlapping with TiO 2 major peaks, or peak masking. [21,27] Bhardwaj reported that the good dispersion and strong heterojunction creation between the nanocomposite constituents can be the reason for absence of intensive characteristic diffraction peaks for metals after deposition. [32] However, very small, low intensity and weak 200), (220), and (311) planes of Ag, respectively.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…Further, these results are in good matching with the measured S BET of 55.80, 33.10, and 47.80 m 2 /g for the treated TiO 2 P25, AgÀ P25, and PdÀ P25 nanocomposites; respectively. [21]…”
Section: Bet Surface Area Analysismentioning
confidence: 99%
See 1 more Smart Citation